Perancangan Alat Pendeteksi Gerakan Manusia Menggunakan Sensor Passive Infrared Berbasis Arduino ESP32 dengan Tampilan SMS di Ruangan Mesin Kapal - Zuhal Qad’r Al Auzaiy; Agus Dwi Santoso; Akhmad Kasan Gupron (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The tool that detects human movement has been designed with a passive infrared sensor based on Arduino ESP32 which can send messages via SMS to the ship's security system. This is the background to the need to improve the security system on ships. The aim of this research is to find out the movement in the ship's engine room. This system can find movements. This tool can detect a maximum distance of 6 m. This system consists of software and hardware that allows sensors to detect human actions. The software uses the C+ language program and is used on the Arduino ESP32. Press the switch to activate this device. A message will be sent to the owner's smartphone if there is movement. Methods and tool system design for applied scientific work that will be carried out using prototype research methods. Prototype research methods are used to produce certain products, and test their effectiveness. The results of the research in this applied scientific work are the level of accuracy of the PIR sensor which detects human movement at a maximum distance of 6 meters and sim800L as a message sender to Android. Beyond that the data is unreadable and invalid.